Occupational physical activities and osteoarthritis of the knee. - Coggon, D; Croft, P; Kellingray, S; Barrett, D; McLaren, M; Cooper, C (2000)
OBJECTIVE: To assess the risk of knee osteoarthritis (OA) associated with kneeling, squatting, and other occupational activities. METHODS: We compared 518 patients who were listed for surgical treatment of knee OA and an equal number of control subjects from the same communities who were matched for sex and age. Histories of knee injury and occupational activities were ascertained at interview, height and weight were measured, and the hands were examined for Heberden's nodes. Data were analyzed by conditional logistic regression. RESULTS: After adjustment for body mass index (BMI), history of knee injury, and the presence of Heberden's nodes, risk was elevated in subjects who reported prolonged kneeling or squatting (odds ratio [OR] 1.9; 95% confidence interval [95% CI] 1.3-2.8), walking >2 miles/day (OR 1.9; 95% CI 1.4-2.8), and regularly lifting weights of at least 25 kg (OR 1.7; 95% CI 1.2-2.6) in the course of their work. The risks associated with kneeling and squatting were higher in subjects who also reported occupational lifting, and appeared to interact multiplicatively with the risk conferred by obesity. People with a BMI of > or =30 kg/m2 whose work had entailed prolonged kneeling or squatting had an OR of 14.7 (95% CI 7.2-30.2), compared with subjects with a BMI <25 kg/m2 who were not exposed to occupational kneeling or squatting. CONCLUSION: There is now strong evidence for an occupational hazard of knee OA resulting from prolonged kneeling and squatting. One approach to reducing this risk may lie in the avoidance of obesity in people who perform this sort of work.